The daily evening and morning offering (Agnihotra) according to the Brāhmanas - Bodewitz, Hendrik Wilhelm 1939-2022 (Orientalia Rheno-Traiectina, 1976)
Indien -- Veden -- Brahmanas -- Ritual -- Opfer -- Opferzeremonie -- Feueropfer -- Feuerzeremonie -- Feuerritual -- Sonnenaufgang -- Sonnenuntergang